Glycoprotein D of bovine herpesvirus 5 (BoHV-5) confers an extended host range to BoHV-1 but does not contribute to invasion of the brain - Gabev, Evgeni; Tobler, Kurt; Abril, Carlos; Hilbe, Monika; Senn, Claudia; Franchini, Marco; Campadelli-Fiume, Gabriella; Fraefel, Cornel; Ackermann, Mathias (Journal of virology, 2010)
Bovine herpesvirus 1 (BoHV-1) and BoHV-5 are closely related pathogens of cattle, but only BoHV-5 is considered a neuropathogen. We engineered intertypic gD exchange mutants with BoHV-1 and BoHV-5 backbones in order to address their in vitro and in vivo host ranges, with particular interest in invasion of the brain. The new viruses replicated in cell culture with similar dynamics and to titers comparable to those of their wild-type parents. However, gD of BoHV-5 (gD5) was able to interact with a surprisingly broad range of nectins. In vivo, gD5 provided a virulent phenotype to BoHV-1 in AR129 mice, featuring a high incidence of neurological symptoms and early onset of disease. However, only virus with the BoHV-5 backbone, independent of the gD type, was detected in the brain by immunohistology. Thus, gD of BoHV-5 confers an extended cellular host range to BoHV-1 and may be considered a virulence factor but does not contribute to the invasion of the brain.